CRISPR/CAS- RNACHEMICALLY MODIFIED GUIDE RNAS FOR CRISPR/CAS-MEDIATED GENE REGULATION - HENDEL AYAL; DELLINGER DOUGLAS J; KAISER ROBERT; CLARK JOE; BAK RASMUS O; MYERSON JOEL; PORTEUS MATTHEW H; RYAN DANIEL E (2024)
본 발명은 세포에서 표적 핵산(예를 들어, 표적 DNA 또는 표적 RNA)의 CRISPR/Cas-기반 유전자 조절(예를 들어, 게놈 편집 또는 유전자 발현)을 유도하기 위한 방법에 관한 것이다. 상기 방법은, 생체외 치료에 사용하기 위해 1차 세포에서 또는 생체내 치료에 사용하기 위해 대상내 세포에서 표적 핵산의 유전자 조절을 증대시키는 변형된 단일 가이드 RNA(sgRNA)를 사용하는 것을 포함한다. 또한, 본원에서는 유전자 질환과 연관된 표적 유전자에서의 돌연변이를 교정하기에 충분한 양의 변형된 sgRNA를 투여함으로써 대상에서 유전자 질환을 예방하거나 치료하는 방법이 제공된다. Provided herein are methods for inducing CRISPR/Cas-based gene regulation (e.g., genome editing or gene expression) of a target nucleic acid (e.g., target DNA or target RNA) in a cell. The methods include using modified single guide RNAs (sgRNAs) that enhance gene regulation of the target nucleic acid in a primary cell for use in ex vivo therapy or in a cell in a subject for use in in vivo therapy. Additionally, provided herein are methods for preventing or treating a genetic disease in a subject by administering a sufficient amount of a modified sgRNA to correct a mutation in a target gene associated with the genetic disease.